Stability of fodder yield in various types of maize (Zea mays) under rainfed conditions - REDDY, P RAGHU; SANKAR, G MARUTHI; VENKATESWARLU, S (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted during rainy season of 1991-94 at Hyderabad on 8 genotypes of maize (Zea maysL.) for their stability in fodder yield. The gengtypes (G) in and environment (E) varied significantly, the latter in alinear manner. The G X E interaction was highly significant for the linear portion as well as the non-linear portion butwith a pre-dominance of the former indicating that the genotypes responded in a linear manner with some of thesehaving non-predictable nature. The high-yielding genotype 'African Tall' was found to be better adaptable to good orfavourable environments, while 'Varon' (a synthetic) to poorer environment. The double-cross hybrid 'DHM 105' wasfound to be stable over both poor and better environment having general adaptability.